Inhibition of lipid and protein oxidation in raw ground pork by Terminalia arjuna fruit extract during refrigerated storage - Chauhan, Pranav (Asian-Australas J Anim Sci, 2019)
OBJECTIVE: Terminalia arjuna plant, specially its leaves, bark, and roots, are widely used in traditional herbal medicine due to presence of bioactive components and being a rich source of natural antioxidants. But its fruit has not been used for any such purposes despite its potential to retard oxidation. Hence, the antioxidant potential of Arjuna fruit extract (AFE) in retarding lipid and protein oxidation of raw ground pork was evaluated during refrigerated storage for 9 days. METHODS: The AFEs were prepared using different solvents viz. ethanol (EH), water, ethanol: water (60:40) and methanol:hot water (60:40). The AFEs were analysed for total phenolic content (TPC), 2, 2-diphenyl-1-picrylhydrazyl radical scavenging activity and reducing power. Water extract (WE) and ethanol-water extract (EH-WE) were selected and incorporated at 1.0% into freshly minced pork meat and compared with a synthetic antioxidant, in retarding lipid and protein oxidation during storage. RESULTS: The TPC in AFEs using different solvents ranged from 11.04 to 16.53 mg gallic acid equivalents/g and extracts exhibited appreciable scavenging activity ranging from 50.02% to 58.62%. Arjuna extracts significantly (p<0.05) improved the colour score of meat samples by reducing the formation of metmyoglobin during storage. Both the AFEs (WE and EH-WE) significantly (p<0.05) lowered the thiobarbituric acid reactive substances value, peroxide formation and formation of protein carbonyls in raw pork than control sample during storage. Upon sensory evaluation of all samples, it was found that AFE treatment could prolong the storage period of meat samples, without influencing the colour and odour score, up to 6 days. CONCLUSION: AFEs used at 1% improved the oxidative stability, colour and odour score and prolonged the refrigerated shelf life of ground pork up 6 days. Therefore, AFE could be explored as an alternative natural antioxidant in retarding lipid and protein oxidation in meat products.